The readiness evaluation on food industries to implement mandatory Malaysia halal certification scheme (MHCS) - Abu Bakar, Ibrahim; Man, Sa'adan (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Food industries in Malaysia have implemented Malaysia Halal Certification Scheme (MHCS) on voluntary basis for almost 50 years. This long experience should be exploited to enhance the implementation of MHCS as mandatory and involve wider categories of food industries. Aim: This study aimed to evaluate the readiness level of food industries in Malaysia for the implementation of mandatory MHCS. Methods: About 514 food companies in Malaysia from almost all categories of food premises involved in this study. All the companies were structured randomly selected and the study data were collected using a special pilot tested questionnaire. The data were then statistically analysed using computer program SPSS 25.0 of Windows. Results: The study showed that Malaysia food industries are at 64.0% ready (moderately high level) to implement mandatory MHCS. The level was not influenced significantly by location (state and area of the premises) factor. The type of food premises as well as gender, age, marital status, level of education, race and religion factors showed only small or very small effect on the readiness level. Only educational level, racial and religious factors have some impacts of more than ten percent. Food company owners and food handlers who received high school education show to have highest readiness level. The same goes to Malays and Muslims respondents. On the other hand, food company owners and food handlers who only got primary school education show to have the lowest readiness level. The same goes to Indian respondents as well as Christian and Hindu respondents. Conclusion: The finding of this study should be considered by Malaysia government in the implementation of mandatory MHCS in the future.